2018
DOI: 10.3389/fmars.2018.00336
|View full text |Cite
|
Sign up to set email alerts
|

Marine Threats Overlap Key Foraging Habitat for Two Imperiled Sea Turtle Species in the Gulf of Mexico

Abstract: Effective management of human activities affecting listed species requires understanding both threats and animal habitat-use patterns. However, the extent of spatial overlap between high-use foraging areas (where multiple marine species congregate) and anthropogenic threats is not well-known. Our modeling approach incorporates data on sea turtle spatial ecology and a suite of threats in the Gulf of Mexico to identify and map "hot spots" of threats to two imperiled turtle species. Of all 820 "high" threats grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…In the absence or in the case of poor quantitative and geographic data, which is common in lesser developed countries, our method has the advantage of allowing manually curated and expert knowledge to be used in the model. Love et al (2017) and Hart et al (2018) assessed a spatially explicit impact score for Kemp's ridley Lepidochelys kempii and loggerhead turtles Caretta caretta after combining different in-water and terres- trial threats in the northern Gulf of Mexico. While this assessment is comparable to the potential impact maps that we obtained, the numerical and conceptual approach differs in that it considers only one species at a time and does not include all the terms specified by the ecological vulnerability formula.…”
Section: Methodological Approachmentioning
confidence: 99%
“…In the absence or in the case of poor quantitative and geographic data, which is common in lesser developed countries, our method has the advantage of allowing manually curated and expert knowledge to be used in the model. Love et al (2017) and Hart et al (2018) assessed a spatially explicit impact score for Kemp's ridley Lepidochelys kempii and loggerhead turtles Caretta caretta after combining different in-water and terres- trial threats in the northern Gulf of Mexico. While this assessment is comparable to the potential impact maps that we obtained, the numerical and conceptual approach differs in that it considers only one species at a time and does not include all the terms specified by the ecological vulnerability formula.…”
Section: Methodological Approachmentioning
confidence: 99%
“…However, it was not possible to overcome spatial biases in sample collection and as a result this may represent the greatest source of bias in our analysis. Kemp's ridley sea turtles forage in a wide range of shallow, benthic marine habitats, including a substantial part of the continental shelf (Shaver et al, 2013;Hart et al, 2018). Unfortunately, few studies have characterized invertebrate stable isotope values for continental shelf habitats resulting in greater prevalence of estuarine and coastal organisms in our prey isotopic dataset.…”
Section: Regional Diet Variationmentioning
confidence: 99%
“…Satellite data were available for download on the Wildlife Computers Portal. 1 We used a hierarchical SSM (Jonsen et al, 2003;Patterson et al, 2008) to characterize the movements of all turtles, following our previous studies where we determined foraging and inter-nesting periods for some of these same turtles (Hart et al, 2012(Hart et al, , 2013(Hart et al, , 2014(Hart et al, , 2015(Hart et al, , 2018a. Specifically, we applied a model used by Breed et al (2009) that estimates model parameters by Markov Chain Monte Carlo (MCMC) using WinBUGS via the software program R. As input into the model, we used all tracking data except for locations defined as Location Class Z, which are considered invalid locations (CLS, 2011).…”
Section: Turtle Capture and Ssmmentioning
confidence: 99%
“…Previous work identified where foraging grounds for loggerheads and Kemp's ridleys (Lepidochelys kempii) in the GoM overlapped with eight spatially explicit anthropogenic threats and found that threats for turtles using the southwest coast of Florida included commercial line fishing and harmful algal blooms (HABs; Hart et al, 2018a). However, when we included only threats during the peak migration time of July and August, HABs -which occur usually between August and February 2were only present in a single year and in a relatively small spatial location and so we did not include HABs in our analysis.…”
Section: Anthropogenic Threatsmentioning
confidence: 99%